1983
DOI: 10.3758/bf03202831
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation: Visual-vestibular-somatic interaction

Abstract: Weare able to orient lines with respect to environmentally or egocentrically defined reference axes. To do this we must be able to compensate for disturbances produced by displacement of our eyes relative to other parts of our bodies and for visual disturbances such as tilted frames or moving visual fields. Compensation signals from somatosensory and vestibular receptors were examined in this investigation. Disturbances were produced by tilting the head and by rotating a large visual display. Compensation sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…In a luminous line setting task under a body posi-EXPERIMENT 3 The primary goal of Experiment 3 was to establish what kind of reference frame subjects use for spatial assignment in the absence of task-relevant gravitational cuesthat is, when in a horizontal supine position. tion in which gravitational cues cannot be used as a frame of reference-that is, when subjects are in a supine position (Parker et al, 1983)-a behavioral difference with the upright body position was found when the head was straight, but not when the head was tilted. Relating these results to those in the previous experiments, it seems not implausible that subjects in a supine position with gravitational cues present but task-irrelevant might react similarly to subjects in a situation in which gravitational cues are absent altogether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a luminous line setting task under a body posi-EXPERIMENT 3 The primary goal of Experiment 3 was to establish what kind of reference frame subjects use for spatial assignment in the absence of task-relevant gravitational cuesthat is, when in a horizontal supine position. tion in which gravitational cues cannot be used as a frame of reference-that is, when subjects are in a supine position (Parker et al, 1983)-a behavioral difference with the upright body position was found when the head was straight, but not when the head was tilted. Relating these results to those in the previous experiments, it seems not implausible that subjects in a supine position with gravitational cues present but task-irrelevant might react similarly to subjects in a situation in which gravitational cues are absent altogether.…”
Section: Discussionmentioning
confidence: 99%
“…When the gravitational, the body-defined, and the retinally defined verticals were brought into conflict by varying the head and body positions during a luminous line setting task, deviations from the objective body-defined vertical were smaller in the vertical body position than in the supine body position when the head was straight (Parker, Poston, & Gulledge, 1983;Templeton, 1973), but they were equally large when the head was tilted (Parker et al, 1983). From the combined studies, it seems that, although in principle other reference systems can be used, gravitational information is dominant when it comes to orientation in space or to the assignment of verticality to visually perceived information.…”
mentioning
confidence: 98%
“…However, when the tilt is restricted to the head, results vary from one experiment to another. They are E effects (Day & Wade, 1969;Wade, 1968Wade, , 1969Witkin & Asch, 1948a), A effects (Dichgans, Diener, & Brandt, 1974;Parker, Poston, & Gulledge, 1983), or occasionally no general effect (DiLorenzo & Rock, 1982;Merker & Held, 1981).…”
Section: Aubert and Miiller Effectsmentioning
confidence: 99%
“…The dissimilarities observed between A-effects and E-effects are usually explained by a difference in the perceived body tilt. It is often argued that small angles of body tilt are associated with an overestimation of one's own body position (E-effect) and large angles of body tilt are associated with an underestimation (A-effect; Day & Wade, 1969;Howard & Templeton, 1966;Parker, Poston, & Gulledge, 1983). Thereby, it is assumed that the SVV and the perception of body position are based on the same reference for the physical vertical (Van Beuzekom & Van Gisbergen, 2000).…”
mentioning
confidence: 99%